Investigation of Seepage Meter Measurements in Steady Flow and Wave Conditions. Issue 6 (18th November 2014) - Russoniello, Christopher J.; Michael, Holly A.
Abstract: Water exchange between surface water and groundwater can modulate or generate ecologically important fluxes of solutes across the sediment‐water interface. Seepage meters can directly measure fluid flux, but mechanical resistance and surface water dynamics may lead to inaccurate measurements. Tank experiments were conducted to determine effects of mechanical resistance on measurement efficiency and occurrence of directional asymmetry that could lead to erroneous net flux measurements. Seepage meter efficiency was high (average of 93%) and consistent for inflow and outflow under steady flow conditions. Wave effects on seepage meter measurements were investigated in a wave flume. Seepage meter net flux measurements averaged 0.08 cm/h—greater than the expected net‐zero flux, but significantly less than theoretical wave‐driven unidirectional discharge or recharge. Calculations of unidirectional flux from pressure measurements (Darcy flux) and theory matched well for a ratio of wave length to water depth less than 5, but not when this ratio was greater. Both were higher than seepage meter measurements of unidirectional flux made with one‐way valves. Discharge averaged 23% greater than recharge in both seepage meter measurements and Darcy calculations of unidirectional flux. Removal of the collection bag reduced this net discharge. The presence of a seepage meter reduced the amplitude of pressure signals at the bed and resulted in a nearly uniform pressure distribution beneath the seepage meter. These results show that seepage meters may provide accurate measurements of both discharge and recharge under steady flow conditions and illustrate the potential measurement errors associated with dynamic wave environments.